Monitoring in adaptive co-management: Toward a learning based approach - Cundill, Georgina; Fabricius, Christo (Journal of Environmental Management, 2009)
The recognition of complexity and uncertainty in natural resource mana gement has lead to the development of a wealth of conceptual framework s aimed at integrated assessment and complex systems monitoring. Relat ively less attention has however been given to methodological approach es that might facilitate learning as part of the monitoring process. T his paper reviews the monitoring literature relevant to adaptive co-ma nagement, with a focus on the synergies between existing monitoring fr ameworks, collaborative monitoring approaches and social learning. The paper discusses the role of monitoring in environmental management in general, and the challenges posed by scale and complexity when monito ring in adaptive co-management. Existing conceptual frameworks for mon itoring relevant to adaptive co-management are reviewed, as are lesson s from experiences with collaborative monitoring. The paper concludes by offering a methodological approach to monitoring that actively seek s to engender reflexive learning as a means to deal with uncertainty i n natural resource management.
Keywords: Adaptive co-management; Collaborative monitoring; Complexity; Social learning